Production and productivity components of hybrid rice dry compared to conventional three cultivars (2010)
This research aimed to evaluate the yield and productivity of Ecco rainfed compared to conventional cultivars BRS Primavera, BRS Sertanejaand Cambará in Vilhena and Cerejeiras cities, Rondonia state. The experiment was completely conducted in random with four replications. The experiments were conducted in November, 2009, one in the Experimental Farm at Faculdade da Amazônia, in Vilhena city, Rondonia state, located at latitude S 12°44'26" and longitude W 60°08'45", and the other at the Experimental Field of Faculdade da Amazônia in Cerejeiras-RO, located at S 13°11'19,6" latitude and W 060°51'43,9" longitude. The variables were: tillering, number of whole grains and chochos per panicle, 1000 grain weight, yield in bags of 60 kg per hectare and yield of whole grains. The hybrid cultivar Ecco is the most suitable for cultivation in the two regions, because it showed better tillering, greater efficiency in grain filling, greater weight of 1000 grains and consequently higher productivity in both regions, besides a high yield of whole grains in relation to other cultivars.